2022
DOI: 10.1111/bcp.15533
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication in pregnancy and lactation and early development of exposed children

Abstract: There is still limited knowledge about alterations of blood concentrations of psychotropic drugs during pregnancy, the transfer of psychotropic drugs into breastmilk and the effects on exposed children. We investigated changes in concentrations of psychopharmacological medication during pregnancy and lactation in serum and breastmilk at different time points in a naturalistic sample of 60 mothers and observed the development of the exposed children in the first 12 months. We found a decrease in serum concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Leutritz et al 42 . also reported a decreased exposure of sertraline in 11 patients during pregnancy.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Leutritz et al 42 . also reported a decreased exposure of sertraline in 11 patients during pregnancy.…”
Section: Resultsmentioning
confidence: 91%
“…Sertraline is metabolized by multiple enzymes, which are altered in different ways during pregnancy (e.g., increased CYP2B6, CYP3A4, and CYP2D6 activity but decreased CYP2C19 activity), 13 making it difficult to predict the overall effect on sertraline concentrations. Four studies reported lower sertraline concentrations in late pregnancy compared to postpartum, though only one study demonstrated statistical significance 42,44–46 . In contrast, one study reported a significant increase in maternal sertraline concentrations during pregnancy and higher concentrations in the third trimester than in nonpregnant individuals 39 .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations